83.1k views
1 vote
Simplify the expression.

5(8x-10)-10x+25(8x−10)−10x+2

50x - 48


50x + 48


30x - 48


30x + 52

witch one is correct

User Speckpgh
by
5.7k points

1 Answer

3 votes
5(8x - 10) - 10x + 25(8x - 10) - 10x + 2
= (40x - 50) - 10x + (200x - 250) - 10x + 2
= 40x - 50 - 10x + 200x - 250 - 10x + 2
= (grouping like terms together)
= 40x - 10x + 200x - 10x - 50 - 250 + 2
= 220x - 298
User Joseph Rex
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.